Contamination and ecological risk assessment of trace elements in sediments of the rivers of Sundarban mangrove forest, Bangladesh. Issue 1 (15th November 2017) - Islam, M.A.; Al-mamun, A.; Hossain, F.; Quraishi, S.B.; Naher, K.; Khan, R.; Das, S.; Tamim, U.; Hossain, S.M.; Nahid, F.
Abstract: In this study, total concentrations of 16 trace elements (Al, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Cd, Sb, Hg, Pb, Th and U) in sediments of the rivers of the Sundarban mangrove forest, after the catastrophic oil spill accident in the Sela river of Sundarban, were determined. The overall mean concentrations of V, Cr, Fe and Cd in surface sediments of the Sundarban are remarkably higher than available literature data of those elements. Trace element contamination assessment, using different environmental contamination indices, reveals that As, Sb, Th and U are low to moderately contaminated while Cd is moderately to severely contaminated in the sediments of this area. The multivariate statistical analyses were applied to reveal the origin and behavior of the elements during their transport in the mangrove ecosystem. High Cr, Ni, Cu and As concentrations suggest the risk of potentially adverse biological effects in the ecosystem. Highlights: Total 16 elements in sediments of the Sundarban mangrove forest were determined. The contents of V, Cr, Fe and Cd are higher than those available literature data. Trace element contamination indices and ecological risk of toxicity were assessed. The statistical analyses reveal the origin and transport behavior of the elements.